THE CONCEPT OF FAIRNESS IN THE DIVISION OF NIGHTTIME HOURS: A CASE STUDY OF A WIFE EXPERIENCING NUSYUZ - Wike Sundari; Muhammad Amar Adly (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
This study seeks to comprehend the legal dimensions of polygamy and the rationale for alternating overnight stays (qasm) as delineated in the book Fathul Qorib, especially in instances when a wife is undergoing nusyuz (disobedience). The research uses a literature review methodology by analysing original materials, particularly the book Fathul Qorib. The results show that polygamy is allowed as long as the spouse can be fair and provide maintenance (nafaqah).. In Fathul Qorib, the rotation of turns emphasizes the husband's obligation to equalize overnight stays, provide separate residences, and not violate the established order of turns unless there is a reason justified by Sharia. In cases involving a nusyuz wife, justice in time distribution serves as a means of education and behavioral improvement. Nevertheless, Fathul Qorib asserts that the husband is still obliged to fulfill the rights of a new wife consecutively and must compensate for the rotation time if a violation occurs. This research concludes that a fair division of time aims to ensure each wife receives proper physical and emotional attention, thereby preventing harm within the household.Keywords: Polygamy; Marriage; Nusyuz;.